Investigation of Fresh and Hardened Characteristics of Self-Compacting Concrete with the Incorporation of Ethylene Vinyl Acetate and Steel-Making Slag - Kashif Ali Khan; Hassan Nasir; Muhammad Alam; Sajjad Wali Khan; Izhar Ahmad; Zia Ur Rehman (Advances in Civil Engineering)
Advancement in the construction industry causes decline in the availability of natural resources, and this decline can be overcome by utilization of the available raw materials. This study is focused on the combined effects of ethylene vinyl acetate (EVA) and ladle furnace slag (LFS) on fresh and hardened characteristics of self-compacting concrete (SCC) by replacing some fraction of cement and sand. The characteristics of SCC in its fresh state are investigated by workability, while hardened characteristics are investigated by elastic modulus and compressive, tensile, and flexural strength. The findings showed that the workability is enhanced by the incorporation of EVA, while decreased with LFS. Furthermore, all the strength properties were enhanced at all the replacement levels of EVA and LFS except for the splitting tensile strength. The utmost gain in elastic modulus and compressive, tensile, and flexural strength was up to 18, 20, 10, and 15% more by increasing the dosage of LFS while keeping EVA constant.